Alocação eficiente de fontes de água em uma residência - Jesus, Thiago Barbosa (2018)
This study is structured in four chapters-articles dedicated to identify and minimize the Energy Intensity (EI) of water supply. In the first article we aimed to find the EI of Rainwater Harvesting Systems (RWHS). The results showed the existence an optimal point between the reservoir volumes from 1.0∙10³ L to 2.5∙10³ L, adopting the catchment areas tested with equal demand of 4.8∙10² L∙(residence∙day)-1. The calculated energy performance was 0.51 kWh∙m-3 at 0.90 kWh∙m-3. For the mean value of catchment area of 80 m² the minimum EI was 0.72 kWh∙m-3 with a reservoir of 1.75∙10³ L. The second article explored different materials for the various RWHS components, including the gutter, reservoir and energy source. Beteween these components, the most relevant was the reservoir, followed by gutter and energy source. The least intensive configuration was the use of the polyethylene reservoir, the aluminum gutter and photovoltaic energy, for this scenario the calculated EI was 0.66 kWh∙m-3. The results obtained in this article showed the importance of choosing materials for RWHS, which directly affect the final EI. In the third article we evaluated the use of groundwater with depths ranging from 5 m to 25 m, with EI from 1.74 kWh∙m-3 to 2.97 kWh∙m-3. The well casing and the pump were the most intensive components, with more than 70% participation at all depths. In the three articles elaborated the EI found was lower than the public supply system and the construction phase was the one that mostcontributed to the final EI. This result shows the importance for the choosing components of decentralized supply systems, that these directly affect EI. The fourth article sought to find the best water supply arrangement that would provide the least EI associated with the water supply of a residence. The values found in the articles elaborated within this dissertation were used, complemented with EI data of gray water found in the literature. The public water, rainwater, underground and gray water mix would result in an EI of 2.44 kWh∙m-3 for the supply of a residence with four people in the municipality of Feira de Santana/BA. This figura would represent a reduction of 31% of EI in relation to the public system and 72% of the water consumption of the public system